2019
DOI: 10.1021/acs.jpcb.9b03314
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Cholinium Based Protic Ionic Liquids through Molecular Dynamics

Abstract: An analysis of the complex proton transfer processes in certain protic ionic liquids, based on amino acid anions, has been carried out through ab initio molecular dynamics in the view of finding naturally conductive and pure mediums. The systems analyzed here might serve as chemical prototypes for pure and dry ionic liquids where mobile protons can act as fast charge carriers. We have exploited the natural tendency of these liquids to form a complex network of hydrogen bonds. The presence of such a network all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Even in the simplest AA anions with aliphatic side chains, the computational data do suggest the presence of conspicuous anion-anion pairing through H-bonding of their amino and carboxylate groups (Fedotova et al 2019). Le Donne et al ( , 2019 using AIMD have found a rough but evident correlation between the association energies of the dimeric anion-anion structures and the measured viscosities of the corresponding ChAAILs. A recent work by Khorrami and Kowsari (2020) based on classical MD has further extended the study of these like-charge interactions to the mixtures of ChAAILs with water.…”
Section: Structure and Computational Studiesmentioning
confidence: 99%
“…Even in the simplest AA anions with aliphatic side chains, the computational data do suggest the presence of conspicuous anion-anion pairing through H-bonding of their amino and carboxylate groups (Fedotova et al 2019). Le Donne et al ( , 2019 using AIMD have found a rough but evident correlation between the association energies of the dimeric anion-anion structures and the measured viscosities of the corresponding ChAAILs. A recent work by Khorrami and Kowsari (2020) based on classical MD has further extended the study of these like-charge interactions to the mixtures of ChAAILs with water.…”
Section: Structure and Computational Studiesmentioning
confidence: 99%
“…In other words, if the position of equilibrium ( 1) is not known or uncertain, the possibilities of obtaining a clear-cut answer from simulations are rather limited. Useful indications can certainly be had from the accurate computations of proton transfer energy profiles in isolated pairs, 126,127 and from AIMD simulations, [128][129][130] but the reliable prediction of equilibrium (1) in condensed system still defies a straightforward computational approach.…”
Section: The Problem Of Ionicitymentioning
confidence: 99%
“…For example, the presence of low-Q scattering peaks in the X-ray diffraction patterns indicated that there existed some form of structural aggregation at the nanoscale that calculations on isolated dimers were unable to grasp. 68,69 From some of our recent studies, 129,131 it was clear that the structure of these fluids was determined, not only by the interactions between molecular components of opposite charges, but also by those between likely charged ones. Modeling such balance requires necessarily a great accuracy in the calculation of the interatomic potentials because of the need to properly account for polarization phenomena.…”
Section: Like Charge Aggregation Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their apparent simplicity [6], PILs can sometimes show complex structural patterns and unexpected chemical activity owing to a series of inter-related phenomena such as nano-segregation [7,8], hydrogen bonding [9][10][11][12][13], and tautomerization reactions involving secondary protic functions on the molecular structure [14,15]. The latter, in turn, may spawn proton mobility [16,17].…”
Section: Introductionmentioning
confidence: 99%